Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran IPAS dengan Menerapkan Model Pembelajaran Snowball Throwing di Kelas III SD Negeri Perintis B: Penelitian - Astri Fitriyani; Indriani Fauziah; Rinaldi Yusup (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to review the learning outcomes of students by applying the Snowball Throwing Learning Model in the subject of Social Sciences for grade III Elementary Schools. The research method is using the Classroom Action Research (CAR) method, based on the theory of constructivism. The sample of this study was all grade III students, data collection was carried out through interviews with teachers, observations, tests, questionnaires, and documentation. The results of this study indicate that the Snowball Throwing learning model is effective in improving student learning, where this model can improve students' thinking power, collaboration, and activeness during the learning process. From the results of interviews and observations, students have difficulty in understanding the subject of Social Sciences so that most students get scores below the KKM. The influence of this study is expected to create a perspective on the importance of learning models.